Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1371/journal.ppat.1009588
|View full text |Cite
|
Sign up to set email alerts
|

The Trypanosoma brucei subpellicular microtubule array is organized into functionally discrete subdomains defined by microtubule associated proteins

Abstract: Microtubules are inherently dynamic cytoskeletal polymers whose length and organization can be altered to perform essential functions in eukaryotic cells, such as providing tracks for intracellular trafficking and forming the mitotic spindle. Microtubules can be bundled to create more stable structures that collectively propagate force, such as in the flagellar axoneme, which provides motility. The subpellicular microtubule array of the protist parasite Trypanosoma brucei, the causative agent of African sleepi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 88 publications
2
12
0
Order By: Relevance
“…T. brucei has a number of life cycle developmental forms with characteristic morphologies and substantial remodelling of the cortical cytoskeleton is required for their generation. We identified 10 subdomains of the cortical cytoskeleton (Figure S4D,E), greatly extending the previous discovery of a posterior-ventral domain marked by PAVE1 (Tb927.8.2030) 67,68 , with particular complexity seen in the anterior and posterior tip subdomains. Like the flagellum tip, the cortical cytoskeleton posterior tip maintained its protein cohort over the cell cycle.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…T. brucei has a number of life cycle developmental forms with characteristic morphologies and substantial remodelling of the cortical cytoskeleton is required for their generation. We identified 10 subdomains of the cortical cytoskeleton (Figure S4D,E), greatly extending the previous discovery of a posterior-ventral domain marked by PAVE1 (Tb927.8.2030) 67,68 , with particular complexity seen in the anterior and posterior tip subdomains. Like the flagellum tip, the cortical cytoskeleton posterior tip maintained its protein cohort over the cell cycle.…”
Section: Resultssupporting
confidence: 82%
“…brucei flagellar-driven motility is critical for virulence in the mammalian host and development in the tsetse fly 64,65 . The flagellum and other cytoskeleton-based structures have important functions associated with specific subdomains 25,46,47,[66][67][68] and we identified numerous proteins associated with axoneme, cortical cytoskeleton and FAZ subdomains (Figure S4). In particularly, we showed that the flagellum tip was a complex structure (Figure S4A).…”
Section: Novel Organelle Subdomains: Key Parasite Functions and Life ...mentioning
confidence: 99%
“…In order to localize MyAP with greater precision within the SPC itself, we conducted expansion microscopy on T. cruzi epimastigotes combined with an IFA against the Ty-epitope using our MyAP-Ty complemented line. Utilizing the TAT-1 anti-α-tubulin antibody (26, 27) to highlight parasite microtubules, we were able to demonstrate that MyAP-Ty specifically targets to the microtubule rootlets rather than the membrane tubule of the SPC ( Figure 3E left panel). In addition, we examined the localization of both MyoF-Ty and MyoC-Ty using this same methodology and found that these motors also associated with the SPC microtubules ( Figure 3E middle and right panels respectively) thus validating previous observations of MyoF using immuno-electron microscopy (28).…”
Section: Resultsmentioning
confidence: 99%
“…The reduction of cell size was an unexpected result, though the shape of trypanosomatids depends on subpellicular microtubules (SM) (Sinclair et al, 2021), and T. brucei cell motility seems to shape SM (Sun et al, 2018). Sun et al showed that flagellar detachment caused by RNAi of FLA1BP leads to abnormal SM handedness compared with parasites with a normal flagellar wave.…”
Section: Discussionmentioning
confidence: 99%